VD_FINDINFO LAVAM 2/20 - 10/2020 vom 10. November 2020 - VD Tribunal cantonal (2020)
ALLOCATION SOCIALE, AM, PRIME D'ASSURANCE-MALADIE, UNITÉ ÉCONOMIQUE, CONCUBINAGE | 11 al. 1 LVLAMal, 9 al. 1 LVLAMal, 9 al. 2 LVLAMal, 10 al. 1 let. d LHPS, 9 LHPS